Effects of Electron Beam Irradiation on Zearalenone and Ochratoxin A in Naturally Contaminated Corn and Corn Quality Parameters - Xiaohu Luo; Lijun Qi; Yuntao Liu; Ren Wang; Dan Yang; Ke Li; Li Wang; Yanan Li; Yuwei Zhang; Zhengxing Chen (Toxins, 2017)
Zearalenone (ZEN) and ochratoxin A (OTA) are secondary toxic metabolites widely present in grains and grain products. In this study, the effects of electron beam irradiation (EBI) on ZEN and OTA in corn and the quality of irradiated corn were investigated. Results indicated that EBI significantly affected ZEN and OTA. The degradation rates of ZEN and OTA at 10 kGy in solution were 65.6% and 75.2%, respectively. The initial amounts significantly affected the degradation rate. ZEN and OTA in corn were decreased by the irradiation dose, and their degradation rates at 50 kGy were 71.1% and 67.9%, respectively. ZEN and OTA were more easily degraded in corn kernel than in corn flour. Moisture content (MC) played a vital role in ZEN and OTA degradation. High MC was attributed to high ZEN and OTA degradation. The quality of irradiated corn was evaluated on the basis of irradiation dose. L* value changed, but this change was not significant (p > 0.05). By contrast, a* and b* decreased significantly (p < 0.05) with irradiation dose. The fatty acid value increased significantly. The pasting properties, including peak, trough, breakdown, and final and setback viscosities, were also reduced significantly (p < 0.05) by irradiation. Our study verified that EBI could effectively degrade ZEN and OTA in corn. Irradiation could also affect corn quality.